Advertising in a Context Harm Crisis. Issue 3 (21st July 2021) - Robinson, Thomas Derek; Veresiu, Ela
Abstract: Context harm crises concern the challenges of advertising morally sound products in a context that is failing, as during COVID-19. Following Koselleck, we argue that crises interrupt the trajectory of existing social processes, thereby preventing consumers' expected future outcomes. We propose a three-step future framing advertising strategy in response: (1) mourning a future that was lost to facilitate emotional adaptation; (2) reconstructing a new future to facilitate rational action under conditions of ambivalence; and (3) establishing mythologies for future-oriented identity work to facilitate the existential demands of crises. We then discuss health messaging from the perspective of future framing.